Antony and Cleopatra A Shakespeare children's story - Shakespeare, William (USA, 2013)
Antony and Cleopatra is a brilliant drama of love and war by William Shakespeare. Hailed as one of the master playwright's greatest tragedies, the play is set in ancient Rome and Egypt and portrays actual events from Roman History.
shelving location "L"
Keywords: english